ANALISIS PENDAPATAN DAN PROPORSI BAGI HASIL NELAYAN PURSE SEINE BERDASARKAN KAPASITAS KAPAL DI DESA BALIMU KECAMATAN LASALIMU SELATAN KABUPATEN BUTON - Ahmad Syarifuddin; N. Nurdiana A (Jurnal Sosial Ekonomi Perikanan, 2022)
This study aims to determine how much income the fishermen who own the purse seine fishing gear and the profit sharing system get based on the capacity of the ship. This study used a census method with 6 respondents and was carried out in Balimu Village, Lasalimu Selatan District, Buton Regency during the period November 2020. The types of data used were primary data and secondary data. Data were collected using interview techniques, questionnaires, documentation and literature study. The data obtained were analyzed using Revenue analysis (TR = PQ), Cost Analysis (TC = TFC.TVC), Income Analysis (π = TR - TC), and Profit Sharing System Analysis (π = Profit (Rp). The results showed that the highest level was obtained by Mr. Safaria, namely Rp. 500,126,880, while the smallest income was obtained by Mr. Hasanuddin, which was Rp. 128,728,827. The profit sharing system treated by fishermen who owned the purse seine was divided by 50:50, meaning the boat owner. get 50% profit from previous income and 50% for ABK. Keywords: Buton Regency; Purse Seine; Income